Images and Metaphors, Mirrors of Social Concern in the Saga af Viktor ok Blavus - Mester, Annegret (Universität Tübingen, 2004)
Images and Metaphors, Mirrors of Social Concern in the Saga af Viktor ok Blavus I wish to examine how the images and metaphors in the Saga af Viktor ok Blavus reflect the concerns of Icelandic society. Included among the metaphors are the personae which populate the saga. As in the Saints’ legends they are not characters but types and are therefore themselves metaphors. The opening stanzas of the Saga af Viktor ok Blavus comprise a reference to the translated riddarasögur which the anonymous author considers as being instructive. Therefore he expects men to model themselves on the lore propagated by them. By opening the Saga af Viktor ok Blavus with a reference to the riddarasögur, the author places both types of works on the same level. From this we may infer that he considers the Saga af Viktor ok Blavus to be of equal benefit to the audience as the translated works. Moreover, the notion that stories of chivalry provide examples for noble and virtuous behaviour is in accordance with the purpose and aims of the translations realised during the reign of King Hákon gamli whose memory the anonymous author of the Saga af Viktor ok Blavus evokes stating that Hákon, the son of Magnus ‘had many chivalric stories translated into Norwegian from Greek or French’. The only evidence for the purpose of the translations fomented by king Hákon IV is to be found in the first part of the prologue to the Strengleikar where the translator explains that ‘the exemplary conduct and virtues of Marie’s heroes, their nobility and goodness are considered a notable assistance in man’s endeavour to acquire the kingdom of God by means of fitting behaviour and good deeds’. The Saga af Viktor ok Blavus belongs like the translated riddarasögur to a literature written for the members and servants of the royal court. We may therefore take the author’s emphasis on the instructive value of the courtly literature expressed in the opening verses of the Saga af Viktor ok Blavus and the translator’s accentuation of Marie’s heroes as role models in the prologue to the Strengleikar as an indication that the Saga af Viktor ok Blavus is concerned with the court and with kingship. This assumption is further strengthened, as I will show later on, by the striking image of a splendid carpet with a king mounted on a white horse which Viktor perceives when initiating his trajectory from a squanderer who has brought his realm to the brink of ruin to an apt king. But first I want to tackle another question. The Saga af Viktor ok Blavus was written in Iceland. Why should the autonomous Icelandic chieftains who had hitherto adhered to a constitution which shut out royal authority be interested in the questions of king and kingship? In the year 1262 the Icelanders recognised in the thing-assembly the Norwegian king as Iceland’s overlord putting by this act an end to the war between the most powerful families. Despite dissatisfaction with the conditions caused by the union with Norway, the Icelanders never abstained from ratifying their agreement with the Norwegian king. This attitude shows that the Icelanders adhered to the idea prevailing in the rest of Europe that royal rule was a divine institution to which all Christians owed submission. The Christian conception of a state presupposed that a country had a king, who could exercise secular power on God’s behalf. The St Olaf’s cult which had given kingship a special consecration influenced without doubt the Icelandic attitude towards kingship, for the legends about the miracles wrought at the shrine of the sainted Norwegian king were favourite reading among the Icelanders. I have already mentioned that the saga’s concern with kingship is highlighted by the image of a splendid carpet which initiates Viktor’s trajectory towards an apt king. A king mounted on a white horse is on the rug. Viktor has scarcely taken in the scene when the rug comes down. The scene is depicted through the eyes of Viktor who is standing on the ground looking up to the sky. The narrative effect in this passage consists in making the carpet the frame around the central element, the king on the white horse. The narrative device tells us that Blavus is no ordinary man. This impression is strengthened by the form of transportation he employs to move from one place to another, a splendid carpet. The image seems to be taken from the Midrash ‘Solomon and the Ant’. In this Hebrew story Solomon travels through the air on a carpet of silk to all the places he wants. Due to the spectacular means of transportation - a costly flying carpet - the informed reader aligns King Blavus with the Biblical king Solomon. Blavus is no ordinary visitor; he is a king. The King stands as an image of ascent to the highest obtainable rank. To be a king is a metaphor for complete self realisation. Blavus foreshadows what Viktor is going to be at the end of his trajectory. Viktor’s meeting with Blavus may be seen as a catalyst. From the moment of their encounter Viktor feels called upon to accomplish tasks which seem impossible to resolve. Each time he has to find a new way of solving the task he has set for himself. Each time he is uncertain of the outcome, but the helper never fails to appear. All the helpers are somehow connected with Blavus but Blavus is also somehow part of Viktor. This unity between Viktor and Blavus finds expression in their sworn brotherhood and their joined kinship. But since Blavus is part of Viktor, the knight himself has created the precondition for the aid he receives. The link with Solomon is further enhanced by the parallelism the author creates between Blavus and Solomon in the ensuing course of events Blavus displays Solomon’s chief attributes which are wisdom, honour or glory and wealth. Berit Olam states that the term ‘wisdom’ is broader in Hebrew than in English and can include such morally neutral ideas as shrewdness, cleverness, and even skill in handicraft. Blavus displays wisdom when insisting that he alone will have control over both wherever they go because he knows that Viktor excels in bravery but lacks wisdom for world conduct. This evaluation of Viktor’s character is confirmed by his spendthrift habits as former ruler. Blavus’s wisdom also shows in that he proves to be a shrewd and successful bargainer when he offers the aged Samarion a coast town and three castles with tributes in exchange for his fleet. Samarion, delighted with the offer, cedes to him not only his fleet but also the shrewd counsellor Kador who is an expert in all things related to sailing and piracy. The fleet and Kador’s counsel are an indispensable aid in laying the foundation to Blavus and Viktor’s renown and wealth. In Studies in Hebrew Narrative & Poetry Berit Olam draws attention to a progressive darkening of the portrayal of Solomon by moving away from wisdom for the sake of justice to wisdom for the sake of display and gain. Solomon’s wealth once provided prosperity and security for Judah and Israel alike. Now all the gold Solomon accumulates is for the royal coffers. There is no mention of the people’s benefit. The same we may say of Blavus and Viktor. They amass immense wealth in gold and silver, but nothing flows through them to others. They are portrayed as self-centred, surrounded by an aura of glory and wealth. As result of a closer relation with Norway, the Icelanders became more exposed to the ideas of the time prevailing in the rest of Europe. The perfect prince is the central figure in the political thought of the thirteenth and fourteenth century, and numerous treaties have been written on the subject. It is precisely the love of wealth in a ruler which is condemned in many of these treaties. John of Salisbury points out in The Policraticus, which he wrote 1159, that ‘The prince should never forget that he and his money both belong to the people (iv.5), for the love of wealth for its own sake can lead only to great evil’ (vii,16). Gilbert of Tournai wrote in Eruditio Regum et Principum (1259) that ‘great wealth and avarice are to be shunned, because they obscure the glory of the kingdom’ (I,2,4). Love of wealth for its own sake is one of Viktor’s flaws. The trick Fulgida, the maiden king, plays on Viktor may be seen as a punishment for this flaw. At her request he is letting the carpet down into the tree and plucks an apple for her. She uses the opportunity to escape with his wealth back to India. Viktor returns to his kingdom a poor vagrant unrecognised by Blavus who calls him ‘stinking and poor, slim and hungry’. Other images and metaphors which reflect social concerns are the chest in which always one florin must be left, the sleeping potion which is a device used by the maiden king to humiliate Viktor, the fight against Randver and Onunder who represent the deep-rooted establishment of power, the fight against the black berserks who stand for the forces of evil, etc.